Godong Village Government's Leadership in Reducing Villager Mortality in the Covid-19 Pandemic - Maria Margareta Wardani (Journal of Public Administration and Government, 2023)
The paradigm of the spread of Covid-19 in Indonesia has made the central government act quickly to issue a Circular Letter of the Minister of Villages number 8 of 2020 concerning Covid-19 Response Villages and Affirmation of Village Cash Labor Intensive. The Governor of Central Java as the Chairperson of the Task Force for the Acceleration of Covid-19 Handling issued instruction Number 1 of 2020 concerning Community Empowerment in the Acceleration of Covid-19 Handling at the Citizens Association (RW) Level through the Establishment of the "Jogo Tonggo Task Force". The Regional Government of Grobogan Regency issued a circular letter of the Regent of Grobogan Number: 440 /1915/2020 concerning the New Normal Productive and Safe Corona Virus Disease 2019 Policy. The local government calls on the Village Government to be responsible for forming policies and strategies for handling the spread of Covid-19. Godong Village has the highest case fatality rate due to Covid-19 out of 28 villages in Godong Sub-district. This study aims to determine how the leadership of the Godong Village Government in reducing the mortality rate of villagers in the pandemic era. This research uses a descriptive qualitative approach with the SWOT analysis method. The SWOT analysis used in this research is only for mapping the research conditions and not for quantitative analysis. The Godong Village Government issued Decree of the Godong Village Head Number: 7/VII/2020 concerning the Establishment of the Covid-19 Prevention Jogo Tonggo Task Force. The establishment of the Jogo Tonggo Task Force Program and the Godong Village Micro PPKM Command Post is evidence of the success and responsibility of the Godong Village Government in reducing the mortality rate of villagers due to Covid-19. The activeness of the Godong Village Government in coordinating with the joint team to provide 3T (Testing, Tracing, and Treatment) socialization provides awareness and trust for villagers in breaking the chain of Covid-19 transmission. The effectiveness of the program is evidenced by the fact that there are currently no case reports of the mortality rate of Godong Village residents due to Covid-19.